Effects of commercialization of sweetpotato on gender relations and wellbeing among smallholder farmers: Technical workshop to review study findings and develop recommendations for improved programming - Mudege, Netsayi N.; Kebaara, K.; Mukewa, E. (International Potato Center, 2019)
A two‐day technical workshop was organized by the International Potato Center (CIP) and held in Nairobi in November 2018 to review SUSTAIN project study findings (to understand how commercialization of sweetpotato value chains affected the wellbeing of smallholder farmers) and develop recommendations for improved programming. Workshop participants included representatives of NGOs, farmers, government departments, researchers and the private sector from Kenya, Malawi, Mozambique, Tanzania and Rwanda. The workshop provided an opportunity for cross‐learning among the projects represented.